3D Printing and Buildings: A Technology Review and Future Outlook. Issue 1 (2nd January 2018) - Yin, Hongxi; Qu, Ming; Zhang, Haiyan; Lim, YeChan
Abstract : Three-dimensional (3D) printing has drawn attention from professionals in various fields for its ability to efficiently convert virtual concepts to prototypical parts by adding material in layers. Its advantages include speed, direct data conversion, handling of complex geometry, high accuracy, environmental benefits, and cost effectiveness. This paper provides a technology review of state-of-the-art practices in 3D printing applied to the building industry. Two classifications of 3D printing processes in architecture are reviewed along with 3D printed building case studies. Finally, the strengths and weaknesses of each technology are discussed in relation to building construction, along with challenges and future prospects for 3D printing technologies.